Effects of L-tyrosine and carbohydrate ingestion on endurance exercise performance - Chinevere, T. D.; Sawyer, R. D.; Creer, A. R.; Conlee, R. K.; Parcell, A. C. (Journal of Applied Physiology, 2002)
To test the effects of tyrosine ingestion with or without carbohydrate supplementation on endurance performance, nine competitive cyclists cycled at 70% peak oxygen uptake for 90 min under four different feeding conditions followed immediately by a time trial. At 30-min intervals, beginning 60 min before exercise, each subject consumed either 5 ml/kg body wt of water sweetened with aspartame [placebo (Pla)], polydextrose (70 g/l) (CHO), L-tyrosine (25 mg/kg body wt) (Tyr), or polydextrose (70 g/l) and L-tyrosine (25 mg/kg body wt) (CHO+Tyr). The experimental trials were given in random order and were carried out by using a counterbalanced double-blind design. No differences were found between treatments for oxygen uptake, heart rate, or rating of perceived exertion at any time during the 90-min ride. Plasma tyrosine rose significantly from 60 min before exercise to test termination (TT) in Tyr (means ± SE) (480 ± 26 µmol) and CHO+Tyr (463 ± 34 µmol) and was significantly higher in these groups from 30 min before exercise to TT vs. CHO (90 ± 3 µmol) and Pla (111 ± 7 µmol) (P < 0.05). Plasma free tryptophan was higher after 90 min of exercise, 15 min into the endurance time trial, and at TT in Tyr (10.1 ± 0.9, 10.4 ± 0.8, and 12.0 ± 0.9 µmol, respectively) and Pla (9.7 ± 0.5, 10.0 ± 0.3, and 11.7 ± 0.5 µmol, respectively) vs. CHO (7.8 ± 0.5, 8.6 ± 0.5, and 9.3 ± 0.6 µmol, respectively) and CHO+Tyr (7.8 ± 0.5, 8.5 ± 0.5, 9.4 ± 0.5 µmol, respectively) (P < 0.05). The plasma tyrosine-to-free tryptophan ratio was significantly higher in Tyr and CHO+Tyr vs. CHO and Pla from 30 min before exercise to TT (P < 0.05). CHO (27.1 ± 0.9 min) and CHO+Tyr (26.1 ± 1.1 min) treatments resulted in a reduced time to complete the endurance time trial compared with Pla (34.4 ± 2.9 min) and Tyr (32.6 ± 3.0 min) (P < 0.05). These findings demonstrate that tyrosine ingestion did not enhance performance during a cycling time trial after 90 min of steady-state exercise.